2011
DOI: 10.1128/jvi.05703-11
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular Stomatitis Virus Oncolytic Treatment Interferes with Tumor-Associated Dendritic Cell Functions and Abrogates Tumor Antigen Presentation

Abstract: Oncolytic virotherapy is a promising biological approach to cancer treatment that contributes to tumor eradication via immune-and non-immune-mediated mechanisms. One of the remaining challenges for these experimental therapies is the necessity to develop a durable adaptive immune response against the tumor. Vesicular stomatitis virus (VSV) is a prototypical oncolytic virus (OV) that exemplifies the multiple mechanisms of oncolysis, including direct cell lysis, cellular hypoxia resulting from the shutdown of tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 37 publications
2
24
0
Order By: Relevance
“…In summary, we show that human melanomas are an attractive selective target for VSV-mediated direct oncolysis. The high degree of direct oncolysis in human primary melanoma complements previous work showing that the VSV can initiate or enhance an immune attack on mouse melanoma (26,51,54,55,66).…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…In summary, we show that human melanomas are an attractive selective target for VSV-mediated direct oncolysis. The high degree of direct oncolysis in human primary melanoma complements previous work showing that the VSV can initiate or enhance an immune attack on mouse melanoma (26,51,54,55,66).…”
Section: Discussionsupporting
confidence: 65%
“…Most previous reports on VSV and melanoma focused on mouse melanoma tumors in syngeneic models (25,26,51,52). The most commonly used B16 mouse melanoma model has been referred to in some studies as VSV resistant or partially resistant (24), whereas in others it was shown to be VSV susceptible (53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, although several reports showed that oncolytic VSV potently activates DCs (22,(24)(25)(26), a recent study by Leveille and colleagues showed that, in contrast, VSV infects and kills DCs and thus impedes antitumor immunity (27). Moreover, while many studies have documented that VSV elicits antitumor immunity, Willmon and colleagues showed that VSV subverts host immunity by engaging a population of myeloid-derived suppressor cells (MDSC; ref.…”
Section: Ovs Break Innate and Adaptive Immune Tolerance Toward Tumorsmentioning
confidence: 99%
“…99 VSV interferes with tumor dendritic cell function and blocks tumor antigen presentation. 100 Therefore, adjustments need to be made if VSV treatment is combined with other types of immunotherapy regimens. …”
Section: Vsvmentioning
confidence: 99%